Cytokine-based immunotherapy for gastric cancer: targeting inflammation for tumor control - Mathan Muthu Chinakannu Marimuthu; Bhavani Sowndharya Balamurugan; Vickram Agaram Sundaram; Saravanan Anbalagan; Hitesh Chopra (Exploration of Targeted Anti-tumor Therapy)
Emerging cancer immunotherapy methods, notably cytokine-based ones that modify immune systems’ inflammatory reactions to tumor cells, may help slow gastric cancer progression. Cytokines, tiny signaling proteins that communicate between immune cells, may help or hinder cancer growth. Pro-inflammatory cytokines encourage tumor development, whereas antitumor ones help the host reject cancer cells. This study considers cytokine-targeted methods for gastric cancer pro-inflammatory and antitumor immune responses. Researchers want to renew immune cells like cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells by delivering cytokines like interleukin-2 (IL-2), interferons (IFNs), and tumor necrosis factor-alpha (TNF-α) to activate inflammatory pathways and combat tumors. Since cytokines have significant pleiotropic effects, their therapeutic use is difficult and may cause excessive systemic inflammation or immunological suppression. This review covers current advancements in synthetic cytokines, cytokine-conjugates, and local administration of these aimed to enhance the therapeutic index: increase the potential to kill cancer cells while minimizing off-target damage. The study examines the relationship between cytokines and tumor microenvironment (TME), revealing the role of immunosuppressive cytokines like IL-10 and transforming growth factor-beta (TGF-β) in promoting an immune-evasive phenotype. These results suggest that inhibitory pathway targeting, and cytokine-based therapy may overcome resistance mechanisms. Cytokine-based immunotherapies combined with immune checkpoint inhibitors are predicted to change gastric cancer therapy and rebuild tumor-immune microenvironment dynamics, restoring antitumor immunity. Comprehensive data from current clinical studies will assist in establishing the position of these treatments in gastric cancer.